Co-production as a tool for realisation of public services - Gawłowski, Robert (Journal of Public Governance, 2018)
Objective: New public governance is one of the most popular paradigms in public administration management. The aim of this article is to examine the co-production of public services, which is gaining interest in many European countries, including Poland, and to find out how co-production is defined, what the reasons to pay attention to this tool are, how we can distinguish between different models of co-production and, last but not least, what the possibilities and drawbacks of introducing it into practice are.Research Design & Methods: The article is a literature review based on the most important public management journals.Findings: In conclusion, the author shows new ways of defining co-production and presents a proposal for further research strategies for the co-production of public services.Implications / Recommendations: The meaning of co-production of public services has varied over the last few years due to the fact that various new elements have emerged. Therefore there is still a huge field, to cover such as conducting research about the use of social media in the co-production of public services.Contribution / Value Added: The most recent literature review about co-production was conducted by Vooberg in 2014. As a result, this article refreshes the knowledge about it and proposes a new research agenda for the future.Article Classification: Theoretical article: original literature review.JEL classification: R50